Pengaruh Tata Kelola Perusahaan Terhadap Struktur Modal Di Perusahaan Consumer Non Cyclical - Muhimah, Khoirul; Ardana, I Dewa Ayu Nadya Dhanari Kirana; Lestari, Henny Setyo; Leon, Farah Margaretha (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
The purpose of this research is to analyze and provide a deeper understanding of the influence of corporate governance elements on the capital structure of non-cyclicals consumer companies listed on the Indonesia Stock Exchange. This research uses quantitative research using secondary data obtained from of company financial statements and company annual reports. This research uses a sample of companies listed on the IDX qith the non-cyclicals consumer sector for thr 2019 – 2023 period. The sample of these was 61 of companies. This results of this research indicate that board size, board meetings, firm size, tangibility, depreciation, and profitability have a negative and significant effect on capital structure. Meanwhile, board committee and age have a positive and significant effect on capital structure. In addition, there is no significant influence between board gender and capital structure.